Tight junction physiology of pleural mesothelium - Markov, Alexander G.; Amasheh, Salah (Frontiers in Physiology, 2014)
Pleura consists of visceral and parietal cell layers, producing a fluid, which is necessary for lubrication of the pleural space. Function of both mesothelial cell layers is necessary for the regulation of a constant pleural fluid volume and composition to facilitate lung movement during breathing. Recent studies have demonstrated that pleural mesothelial cells show a distinct expression pattern of tight junction proteins which are known to ubiquitously determine paracellular permeability. Most tight junction proteins provide a sealing function to epithelia, but some have been shown to have a paracellular channel function or ambiguous properties. Here we provide an in-depth review of the current knowledge concerning specific functional contribution of these proteins determining transport and barrier function of pleural mesothelium.